Kebijakan dan Implementasi Ekonomi Syariah di Arab Saudi (Studi Komparasi Pertumbuhan dan Perkembangan Ekonomi Syariah di Negara Islam) - Permana, Febrian; M, Mukhlis; Y, Yudi; Syahrial, Murah; S, Syahpawi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research examines sharia economic policy and implementation in Saudi Arabia. In this paper, researchers use a qualitative approach with the main data source from library data. The study results show that Saudi Arabia continues to innovate and develop its infrastructure to support sustainable sharia economic growth. The development of the sharia economy in Saudi Arabia is due to effective policies and implementation. Government support, strict regulations, and high public awareness of sharia principles are key factors in this success. Even though it still faces several challenges, the prospects for the sharia economy in Saudi Arabia are very bright and have great potential to continue to grow in the future. With the right strategy, the sharia economy in Saudi Arabia can continue to grow and make a significant contribution to the country's economic diversification and stability.